Kitchen cooking by electroporation - František Kumhála; Jakub Lev; Pavel Kouřím; Jiří Blahovec (Research in Agricultural Engineering, 2022)
Recently, modern non-heating-based food processing alternatives have emerged. The pulsed electric field (PEF) technology is an example, which does not require high temperatures and, in principle, preserves both the nutritional and functional characteristics of the food while possibly improving the taste. Nevertheless, using this technology in kitchen conditions is still a challenge. Thus, the main aim of this work was the development of a kitchen cooking device that uses pure pulse electroporation (without thermal effects). A device powered by a common electrical network was designed. The voltage applied to the electrodes is approximately 150 V. At a food thickness of 3 mm, an intensity of 500 V.cm-1 was achieved, which was sufficient for the electroporation of typical vegetables. Depending on the specific food being treated, the device repeats the pulses until the required degree of the PEF treatment is reached. Preparing a larger amount of food at one time would require great instant power from the device. In order to load the device with less current, the large working area of the electrodes was divided into nine segments. The food is gradually prepared segment by segment. The function of the device is controlled via an electronic programmable control unit. The electroporation of the processed material was achieved with a functional prototype of the designed device, but with some limitations that have to be respected in further development.